Desarrollo local e identidad indígena: crítica a los discursos de la autenticidad - Cisternas Irarrázabal, César (Diálogos Latinoamericanos, 2018)
Endogenous local development emerges as an alternative way to promote an economic activation capable of improving the quality of life of the inhabitants of the territories on the margins of capitalist development. One of its main premises is to rescue and promote local identity, which has often resulted in the valuation of indigenous cultures. In this framework, the present essay reflects critically on the concepts of indigenous culture and identity that frequently figure in local development initiatives for indigenous communities. The article concludes that in many cases static representations of culture are built, which lead to the essentialisation of indigenous identity through discourses of authenticity.